2015
DOI: 10.1111/cdev.12465
|View full text |Cite|
|
Sign up to set email alerts
|

The Moral Reasoning of U.S. Evangelical and Mainline Protestant Children, Adolescents, and Adults: A Cultural–Developmental Study

Abstract: This cultural-developmental interview study examined moral reasoning in relation to religious culture (evangelical, mainline Protestants), age (children, adolescents, adults), and moral issue (public, private; N = 120). Compared to adolescents and adults, children used more Ethic of Autonomy and less Ethic of Community reasoning. With age, differences between religious cultures became pronounced. Mainline adults invoked an Ethic of Divinity for private issues. Evangelical adolescents and adults used this ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…As hypothesized, Divinity concepts were almost exclusively introduced by parents, which is consistent with research on individual moral reasoning that demonstrates the importance of Divinity in the moral reasoning and outlooks of adult members of evangelical Protestant, Mormon, and fundamentalist Baptist churches (Jensen, ,b, ; Jensen & McKenzie, ; Padilla‐Walker & Nelson, ) and the low use of Divinity among young children in these groups (Jensen, ; Jensen & McKenzie, ). For their part, children most often invoked Autonomy concerns in these conversations, especially those relating to literal equality and to an individual's psychological and physical well‐being and interests, which is also consistent with previous research on the individual moral reasoning of children (Eisenberg, ; Jensen & McKenzie, ; Killen & Smetana, ; Kohlberg, ).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…As hypothesized, Divinity concepts were almost exclusively introduced by parents, which is consistent with research on individual moral reasoning that demonstrates the importance of Divinity in the moral reasoning and outlooks of adult members of evangelical Protestant, Mormon, and fundamentalist Baptist churches (Jensen, ,b, ; Jensen & McKenzie, ; Padilla‐Walker & Nelson, ) and the low use of Divinity among young children in these groups (Jensen, ; Jensen & McKenzie, ). For their part, children most often invoked Autonomy concerns in these conversations, especially those relating to literal equality and to an individual's psychological and physical well‐being and interests, which is also consistent with previous research on the individual moral reasoning of children (Eisenberg, ; Jensen & McKenzie, ; Killen & Smetana, ; Kohlberg, ).…”
Section: Discussionsupporting
confidence: 76%
“…Walker, Pitts, Hennig, & Matsuba, 1995). Consistent with this view, research using the Three Ethics Approach has demonstrated that Divinity concepts are especially prioritized in the moral reasoning of adult members of U.S. religious cultures that emphasize scriptural authority, such as evangelical Christians, fundamentalist Baptists, and Mormons (Jensen, 1997a(Jensen, ,b, 1998Jensen & McKenzie, 2016;Padilla-Walker & Nelson, 2015). These adults recruit Divinity concepts to justify and determine a wide range of moral judgments, including their stances on suicide, incest, interracial marriage, and parental use of physical discipline, as well as reallife personal issues from participants' own lives.…”
Section: Divinity In Moral Reasoning Of Us Evangelical Christiansmentioning
confidence: 99%
See 3 more Smart Citations